COVID-19 health certification reduces outgroup bias: evidence from a conjoint experiment in Japan - Yoshiaki Kubo; Isamu Okada (Humanities & Social Sciences Communications, 2022)
Abstract The psychological theory argues that serious threats cause negative attitudes from ingroups to outgroups. However, the factors that can reduce such outgroup bias caused by the health threats of a pandemic are unknown. Here, we provide evidence that health certifications to prove immunity or negative test result for COVID-19 reduce outgroup bias. Using a discrete choice experiment with a randomized conjoint design in Japan, we investigated public attitudes towards inbound travelers entering the country, including foreigners, immigrants, and tourists. We found that travelers carrying a vaccination certificate or a negative test result for COVID-19 have a higher probability or rating of being admitted to the country. These effects are the same size as those for travelers undergoing self-isolation. Thus, our results demonstrate that health certification can mitigate outgroup bias among ingroup members experiencing threats to health due to the COVID-19 pandemic. We anticipate that the findings would support the combined usage of vaccine passports and negative certificates to reopen the international borders.